Kualitas Laba Perusahaan LQ-45 Ditinjau Dari Konservatisme, Investment Opportunity Set, Dan Rasio Pembayaran Dividen - Gde Herry Sugiarto Asana; Made Yudi Darmita; Tiara Kusuma Dewi; Gusti Ayu Made Karmila (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the effect of conservatism, investment opportunity set, and dividend payout ratio on earnings quality in LQ-45 companies on the Indonesia Stock Exchange for the 2019-2020 period. The population in this study are all LQ-45 companies listed on the Indonesia Stock Exchange in the period 2019-2020. The sample in this study was selected by purposive sampling method so that the number of samples in this study were 34 companies. The research method used in this study is quantitative research with data analysis using multiple regression analysis processed with the SPSS 22 statistical program. The conclusions obtained are that the conservatism variable has a significant effect on the earnings quality of LQ-45 companies on the Indonesia Stock Exchange for the 2019-2020 period. The investment opportunity set variable has a significant effect on the earnings quality of LQ-45 companies on the Indonesia Stock Exchange for the 2019-2020 period. The dividend payout ratio variable has a significant effect on the earnings quality of LQ-45 companies on the Indonesia Stock Exchange for the 2019-2020 period.